Somatic Symptoms in Adolescents With an Ill Parent. Issue 4 (28th January 2022) - Elliott, Lindsey C.; Stager, Lindsay M.; Long, Dustin; Goodin, Burel R.; Fobian, Aaron D.
ABSTRACT: Objective: Parent chronic illness may increase somatic symptomology risk in children. The current study examines this association in relation to a variety of chronic illnesses and also considers possible related parental and adolescent background factors. Methods: Secondary analyses used longitudinal data from the University of North Carolina National Longitudinal Study of Adolescent to Adult Health. Interviews were used to assess demographics, adolescent somatic symptoms, living situation, and parental illness and general physical health. Somatic symptoms in adolescents with no ill parents ( n = 2302 adolescents; Mage = 15.3) were compared with adolescents with ill mothers ( n = 2336; Mage = 15.3), ill fathers ( n = 1304; Mage = 15.3), or two ill parents ( n = 3768; Mage = 15.3) using Poisson regression models. We also examined the role of living status, adolescent sex, and parent general physical health on somatic symptom outcomes. Results: Elevated somatic symptoms were observed in adolescents with ill mothers (mean ratio [MR] = 1.15, p = .015) and with both parents ill (MR = 1.10, p < .001). Among adolescents with ill parents, females had more symptoms than males (ill mother: MR = 1.12, p < .001; ill father: MR = 1.23, p < .001; and both parents ill: MR = 1.23, p < .001). Poorer maternal physical health also increased somatic symptom risk (MR = 1.12, p = .02). Longitudinally, adolescents with ill mothers (MR = 1.14, p < .001), ill fathers (MR = 1.13, p < .001), or both parents ill (MR = 1.16, p < .001) had increased somatic symptom risk. Wave I somatic symptoms also increased future risk: ill mother (MR = 1.19, p < .001), ill father (MR = 1.22, p < .001), or both parents ill (MR = 1.20, p < .001). Conclusions: The results highlight that having an ill parent is a risk factor for adolescent somatic symptoms. In addition, other factors such as adolescent sex play an additional role in adolescent somatic symptoms.